Factors impacting on tacit knowledge transfer within Scrum software development teams - Takpuie , Deon (Department of Information Systems, 2015)
Over time, there has been a high failure rate of information systems development (ISD) projects, although Agile development has brought recent improvements. Knowledge management is also known to be one of the critical factors to Agile and project success; however, there are some knowledge transfer studies in Agile development. Therefore, the purpose of this research is to present a theoretical model examining what makes individuals successful at transferring knowledge in teams using Scrum, Agile’s most popular methodology. Twelve semi-structured interviews were conducted at two Scrum companies in Cape Town. Participants interviewed ranged from project managers and Scrum masters to software developers, business analyst and testers. The interviews were all transcribed, then analysed using thematic analysis. The findings produced new relationships between characteristics already well known to impact knowledge transfer as well as newly defined characteristics impacting knowledge transfer in Scrum teams: empathy and articulation skills of the source. The results have shown that the recipient should perceive the person wanting to transfer knowledge as having these characteristics to enable successful knowledge transfer: empathy, motivation, capability, credibility, articulate and ability to communicate enough. The contribution of this study to practice is a list of attributes for HR managers to help improve the knowledge transfer of Scrum team members. The contribution to Scrum research is a new theoretical model that suggests which characteristics a person needs to transfer knowledge successfully in Scrum teams, adapted from Joshi, Sarker and Sarker’s (2007) knowledge transfer model. This model can also be extended in the future by looking more deeply into the new relationships between constructs, such as how motivation together with capability of the source affect knowledge transfer in Scrum teams.